Trace Metal Contents of Vegetables and Fruits of Hyderabad Retail Market - Ismail, F.; Anjum, M.R.; Mamon, A.N.; Kazi, T.G. (Pakistan Journal of Nutrition, 2011)
The heavy metals or trace elements play vital role in the metabolic pathways during the growth and development of plants, when available in adequate concentration. Seasonal fruits and vegetables play a significant role in human nutrition. Food production and its safety is an important aspect of the measure of any nation’s growing economy and it is a popular trend to find out the trace metal contents of vegetables and fruits of local markets throughout the world but still data is lacking in developing countries like Pakistan. The trace metals Co, Zn, K, Na, Fe, Mn, Ca, Mg, Cu, Ni were analyzed in 15 vegetables and fruits (okra, guava, banana, potato, chili paper, onion, tomato, mint, mango, ginger, brinjal, bitter gourd, spinach, carrot) available in the markets of Hyderabad city. Vegetables and fruits selected for the study are commonly consumed by all income groups of Hyderabad city. Mineral contents were determined using Atomic Absorption Spectrometry (AAS). Co was analyzed 0.1038-0.126 mg/100 gm, Zn was 0.44-0.55 mg/100 gm, K 2.3-38.5 mg/100 gm, Na was 1.5-2. Mn was 0.0526-0.1435 mg/100 gm, Ca 0.3-3.35 mg/100 gm, Mg 1.191-32.0 mg/100 gm while Cu 0.1-1.9 mg/100 gm and Ni 0.05-0.18 mg/100 gm where as Fe was found 1.5-29.0 mg/100 gm among all selected vegetables and fruits.